Kritik Tatanan Sosial Kontemporer dalam Lirik Lagu Fstvlst Album Hits Kitsch - Rifandi, Achmad; Rizal, Maulfi Syaiful (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to explain the expressions of social criticism of contemporary society in the lyrics of the song Fstvlst album Hits Kitsch and to identify literary works as a medium for social criticism. The research method uses descriptive qualitative with library study data collection methods and content analysis techniques using Barthes' semiotic approach and literary sociology. The data used is an expression of social criticism that focuses on contemporary societal phenomena in Giddens' theory. The results show that in the lyrics of the song Fstvlst album Hits Kitsch there are 7 expressions of social criticism regarding inequality in social and economic structures, the growth of new values ​​that can eliminate ancestral values, and the loss of civic values ​​due to technological uncertainty and shows how literary works can be a tool to convey criticism and social transformation.